The Relationship Between Export Market Orientation and Firm Performance: A Meta-Analysis of Main and Moderator Effects - Asmat-Nizam Abdul-Talib; Siti-Norhasmaedayu Mohd-Zamani; Ili-Salsabila Abd-Razak (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
Despite various studies into the relationship between performance and the export market orientation, researchers still argue that the current findings remain mixed and inconclusive. In this study, the authors use meta-analytic techniques to examine the relationship between the export market orientation and performance, and the impact of firm-level, industry-level and country-level moderators using a total sample of 10,758 firms in 51 manuscripts from 19 countries. In particular, this study focuses on the nature of incongruent findings across studies conducted in different contexts around the globe. The results reveal that market orientation has a positive overall relationship with exporters’ revenue-based and profit-based performance. Moreover, the moderated regression analysis results indicate that the type of construct (general versus export-specific) and firm size moderate the relationship between the export market orientation and performance. The results also reveal that market turbulence, competitive intensity, and technological turbulence are significant industry-level moderators of the relationship between the market orientation and performance. This study contributes to the body of knowledge by aggregating the empirical evidence from the past literature and providing conclusive results that are beneficial for practitioners and researchers.